A simple method for 3'-labeling of RNA. - Huang, Z (1996)
We describe a simple method for 3'-end labeling RNAs of known sequence. A short DNA template is designed to anneal to the 3'-end of the RNA, with a two nucleotide 5' overhang of 3'-TA-5', 3'-TG-5' or 3'-TC-5'. The Klenow fragment of DNA polymerase I can then cleanly and efficiently extend the 3'-end of the RNA by the incorporation of a single alpha-32P-labeled dATP residue. This method can be used to label one RNA in a mixture of RNAs, or to label 5'-blocked RNAs such as mRNA.